Midwifery knowledge of equitable and culturally safe maternity care for Aboriginal women. Issue 1 (30th December 2020) - Marriott, Rhonda; Reibel, Tracy; Barrett, Terri‐Lee; Bowen, Angela; Bradshaw, Sue; Kendall, Sally; Kotz, Jayne; Martin, Tracy; Monterosso, Leanne; Robinson, Melanie
Abstract: Background: The Birthing on Noongar Boodjar project (NHMRC Partnership Project #GNT1076873) investigated Australian Aboriginal women and midwives' views of culturally safe care during childbearing. This paper reports on midwifery knowledge of Aboriginal women's cultural needs, their perceptions of health systems issues, and their ability to provide equitable and culturally safe care. Method: A qualitative study framed by an Indigenous methodology and methods which supported inductive, multilayered analyses and consensus‐driven interpretations for two clinical midwife data groups (n = 61) drawn from a larger project data set (n = 145) comprising Aboriginal women and midwives. Findings: Midwives demonstrated limited knowledge of Aboriginal women's cultural childbearing requirements, reported inadequate access to cultural education, substituted references to women‐centered care in the absence of culturally relevant knowledge and consistently expressed racialized assumptions. Factors identified by midwives as likely to influence the midwifery workforce enabling them to provide culturally safe care for Aboriginal women included more professional development focused on improving understandings of cultural birth practices and health system changes which create safer maternal health care environments for Aboriginal women. Conclusions: Individual, workforce, and health systems issues impact midwives' capability to meet Aboriginal women's cultural needs. An imperative exists for effective cultural education and improved professional accountability regarding Aboriginal women's perinatal requirements and significant changes in health systems to embed culturally safe woman‐centered care models as a means of addressing racism in health care.